2020
DOI: 10.1111/nph.16709
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity of fungal endophytes across a stress gradient for plants

Abstract: Summary Foliar fungal endophytes are one of the most diverse guilds of symbiotic fungi found in the photosynthetic tissues of every plant lineage, but it is unclear how plant environments and leaf resource availability shape their diversity. We explored correlations between leaf nutrient availability and endophyte diversity among Pinus muricata and Vaccinium ovatum plants growing across a soil nutrient gradient spanning a series of coastal terraces in Mendocino, California. Endophyte richness decreased in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 103 publications
0
26
1
Order By: Relevance
“…2A and B). These are the same classes that have been found in other comparable studies, although the relative proportions differed (Yao et al ., 2019; Oono et al ., 2020). Moreover, we found that the distribution of foliar epiphytic fungal classes significantly differed between pteridophytes and angiosperms/gymnosperms.…”
Section: Resultsmentioning
confidence: 99%
“…2A and B). These are the same classes that have been found in other comparable studies, although the relative proportions differed (Yao et al ., 2019; Oono et al ., 2020). Moreover, we found that the distribution of foliar epiphytic fungal classes significantly differed between pteridophytes and angiosperms/gymnosperms.…”
Section: Resultsmentioning
confidence: 99%
“…However, among species variation in total condensed tannins was greater in plots in seasonal lowland forest (Parida) than aseasonal lowland forest (Bastimentos) (Supplementary Data 2). In addition to examining qualitative aspects of leaf chemical defenses, and components such as volatiles 40 or available carbon and nitrogen 26,41 , future work should consider the relevance of these components in shaping endophyte communities: tannins are climate sensitive 42 and may be important in influencing the host range and richness of tropical endophyte communities at multiple scales. Thus, endophyte richness may be shaped by climate and seasonality both directly and indirectly via host plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent hypothesis proposed by Oono et al [ 46 ], regarding endophyte species richness in the plant surviving under stress conditions. The lower nutrients and higher concentration of toxic compounds can limit the growth of fungi that may increase their diversity and predict species richness of endophyte, due to suppression of otherwise dominating species.…”
Section: Entry and Colonization Of Plants By Microbial Endophytesmentioning
confidence: 99%